Estado e fundo público: a disputa entre o capital e o trabalho pelos recursos orçamentários no Nordeste do Brasil de 2007 a 2014 - ALENCAR JUNIOR, Osmar Gomes de (2018)
This research has analyzed allocation of public fund financial resources between financial bourgeoisie and workers in counties of Northeast region of Brazil, in period from 2007 to 2014, based on capital structural crisis, in which public fund is continuously required to contribute on financial accumulation process. Its main objective was to identify which factions of social classes are most burdened (and favored) on formation and destination of public fund financial resources in periods from 2007 to 2010 and 2011 to 2014. In order to achieve this goal, critical and complete observation of public spending macroeconomic reality was done, in particular regarding amount, direction and relevance of social and financial expenses, from a critical analysis on public budget. It was concluded that working class, on its lowest income faction, was the main provider of public fund, namely social and financial expenses. However, it was less benefited by public policies sustained on social expenses than financial bourgeoisie has appropriated earnings from counties' public debt service.